2020
DOI: 10.1002/ccd.29185
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of drug‐coated balloon angioplasty after directional coronary atherectomy for coronary bifurcation lesions (DCA/DCB registry)

Abstract: Objectives To evaluate the efficacy and safety of additional drug‐coated balloon (DCB) angioplasty after directional coronary atherectomy (DCA) for coronary bifurcation lesions. Background The optimal therapy for bifurcation lesions has not been established, even in the drug‐eluting stent era. DCA possibly prevents plaque and carina shift in bifurcation lesions by plaque debulking; however, the efficacy of combined DCA and DCB (DCA/DCB) for bifurcation lesions remains unclear. Methods This multicenter registry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
51
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(55 citation statements)
references
References 32 publications
3
51
1
Order By: Relevance
“…We consider that DCB angioplasty played an important role in inhibiting neointimal hyperplasia. On the other hand, a recent multicenter registry (DCA/DCB registry) demonstrated the low incidence of TLR at 12 months (3.6%) after DCA following DCB angioplasty for coronary bifurcation lesions even though the mean %PA after DCA was higher than our study (56.3% versus 44.0%) [6]. Based on these results, aggressive debulking of DCA to achieve a %PA less than 50% may not be necessary, if DCA was followed by DCB angioplasty.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…We consider that DCB angioplasty played an important role in inhibiting neointimal hyperplasia. On the other hand, a recent multicenter registry (DCA/DCB registry) demonstrated the low incidence of TLR at 12 months (3.6%) after DCA following DCB angioplasty for coronary bifurcation lesions even though the mean %PA after DCA was higher than our study (56.3% versus 44.0%) [6]. Based on these results, aggressive debulking of DCA to achieve a %PA less than 50% may not be necessary, if DCA was followed by DCB angioplasty.…”
Section: Discussioncontrasting
confidence: 89%
“…Similarly, for LM bifurcation lesions, an improved novel directional coronary atherectomy (DCA) catheter (ATHEROCUT®, Nipro Corporation, Osaka, Japan) has been commercially available in Japan since 2015 and the possibility of stentless strategy using DCA followed by the DCB angioplasty has been investigated. A recent multicenter registry which was conducted in Japan (DCA/DCB registry) reported the efficacy of the DCB angioplasty following DCA for coronary bifurcation lesions [ 6 ]. We investigated the efficacy of stentless strategy by DCB angioplasty following DCA for LM bifurcation lesions.…”
Section: Introductionmentioning
confidence: 99%
“…DCA is now available again since 2014 in Japan and DCB after DCA has become popular to avoid stent implantation [1][2][3] . Since the effect of plaque reduction is more conclusive in DCA…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an improved novel DCA catheter (Atherocut™, NIPRO) has been developed in Japan and was commercialized since 2015. A multicenter retrospective study showed that combination therapy with DCA and DCB could provide an option for stent‐less management of LMT bifurcated lesions in patients with stable coronary artery disease 7 . However, the efficacy of the combination therapy with DCA and DCB in AMI remains unclear.…”
Section: Introductionmentioning
confidence: 99%